2010
DOI: 10.1111/j.1463-1318.2009.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of idiopathic anal fistula using cross‐linked collagen: a prospective phase 1 study

Abstract: In the short-to-medium term, both techniques are safe and equally effective. The results justify continued research into the use of biomaterials to heal anal fistulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 51 publications
0
20
2
Order By: Relevance
“…The collagen fistula plug has a rigid structure that may lead to a poor fit and extrusion as well as interfering with the healing process by leaving unrecognized secondary tracts untreated. Surgisis ® biomaterial (Cook Biotech) is noncross‐linked, possibly leading to bacterial enzymatic degradation in complex environments . In contrast, Permacol™ paste is cross‐linked and more readily resists enzymatic degradation while facilitating fibroblast and vascular ingrowth .…”
Section: Discussionmentioning
confidence: 99%
“…The collagen fistula plug has a rigid structure that may lead to a poor fit and extrusion as well as interfering with the healing process by leaving unrecognized secondary tracts untreated. Surgisis ® biomaterial (Cook Biotech) is noncross‐linked, possibly leading to bacterial enzymatic degradation in complex environments . In contrast, Permacol™ paste is cross‐linked and more readily resists enzymatic degradation while facilitating fibroblast and vascular ingrowth .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported better healing rates in longer tracks, suggesting that shorter tracks (< 3.5 cm) are less likely to retain the glue [155,158], but this has been contradicted in other reports [159][160][161]. Technical errors have been suggested for failure, including inadequate curettage and washout to remove all infected and epithelialized tissue [155,161,162], or incomplete filling of the track with the glue to ensure occlusion [155].…”
Section: Recommendationsmentioning
confidence: 99%
“…The only consistency is that to date no study matches fistulotomy (whether by one or two stages, or seton induced) with regard to long-term fistula eradication rates. The success of fistulotomy is due to its conversion of a chronic enclosed to an acute open wound, thereby allowing the healing cascade to recommence with the potential for progression to complete tissue repair [13]. To achieve similar results without sphincter division, fistula tracts need to be cleared of all granulation tissue or epithelial lining (in order to allow sufficient fibroblast and endothelial cell migration), and the internal opening needs to be appropriately closed.…”
Section: Discussionmentioning
confidence: 99%